Study of the effect of UV radiation on the quality indicators of broiler chicken meat - R. U. Uazhanova; K. E. Tyutebayeva (Алматы технологиялық университетінің хабаршысы, 2022)
This article presents the results of a study of the quality of poultry meat after treatment with ultraviolet radiation during pre-slaughter. At the same time, bactericidal UV irradiators (UV) of 200 MJ/ 254 MJ/cm with an amalgam lamp with a bactericidal radiation power were used to disinfect the air in the poultry house during the outdoor cultivation of broiler chickens on the litter, by indirect irradiation in intermittent mode against the background of intermittent lighting mode. The results of the quality of the organoleptic parameters of the carcass, the chemical composition of the meat, the tasting evaluation of meat and broth, which do not differ from the meat of control chickens, are presented. Studies have shown that the meat of broiler chickens sterilized by UV radiation at doses of 200 MJ / media 254 MJ / cm for various storage periods up to 14 days - chilled meat meets the requirements of SanPiN 2.3.2.1078-01, which gives reason to use it for food purposes without restriction.